Factors influencing undergraduate students' acceptance of a haptic interface for learning gross anatomy. Issue 1 (18th April 2017) - Yeom, Soonja; Choi-Lundberg, Derek L.; Fluck, Andrew Edward; Sale, Arthur
Abstract : Purpose: This study aims to evaluate factors influencing undergraduate students' acceptance of a computer-aided learning resource using the Phantom Omni haptic stylus to enable rotation, touch and kinaesthetic feedback and display of names of three-dimensional (3D) human anatomical structures on a visual display. Design/methodology/approach: The software was developed using the software development life cycle, and was tested by students enrolled in various bachelor degrees at three stages of development within the technology acceptance model, action research and design research methodology frameworks, using mixed methods of quantitative and qualitative analysis. Findings: The learning system was generally well-accepted, with usefulness (72 ± 18, mean ± standard deviation, 0-100 visual analogue scale) rated higher ( p < 0.001) than ease of use (57 ± 22). Ease of use ratings declined across the three versions as modules were added and complexity increased. Students with prior experience with 3D interfaces had higher intention to use the system, and scored higher on identification of anatomical structures. Students with greater kinaesthetic learning preferences tended to rate the system higher. Haptic feedback was considered the best aspect of the system, but students wanted higher spatial resolution and lower response times. Originality/value: Previous research relating to haptic devices in medical and health sciences has largely focused on advanced trainees learning surgical or procedural skills. The present research suggests that incorporating haptic feedback into virtual anatomical models may provide useful multisensory information in learning anatomy at the undergraduate level.